Strengthening Students’ Mental Health through Responsible AI Literacy: The AIMAH Program at Muthahhari Foundation - Iis Rosilah; Dima Noor Ziehad; Ayi M Sirojuddin; Albi Baihaqi; Nurina; Ujang Suyatman (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to explore how responsible artificial intelligence (AI) literacy programs contribute to strengthening students' mental health. Using a qualitative research method with a case study approach at the Muthahhari Foundation, data were collected through in-depth interviews and participatory observation with students from various grade levels, starting from the early years of elementary school. The findings indicate that students are introduced from an early age to the smart use of mobile devices, basic coding, and the creative and productive utilization of AI-based applications. In parallel, the school also implements mental health reinforcement activities such as yoga, regular sports, outdoor learning, and "fun student hours" that support emotional balance and social interaction. The synergy between responsible AI literacy and mental health programs forms a holistic educational approach that prepares students to be not only technologically competent but also mentally resilient in facing the challenges of the digital era. This study recommends the development of an integrated AI literacy curriculum as well as continuous teacher training